Minority ethnic older adults’ perception and behaviour towards COVID-19 public health campaigns in the UK”¯ (Communication & Society, 2024)
In the UK, minority ethnic groups were reported to face the greatest risk from COVID-19. Yet, little is known about their perception and behaviour towards COVID-19 campaigns. This study used 35 semi-structured, in-depth interviews with minority ethnic adults aged 60 or over in England and Wales to explore their motivations for complying with or disregarding official guidance and their evaluations of various campaign content and channels used early in the pandemic. Using Template Analysis, key themes in the interviewees’ discourse were identified, which were subsequently analysed using the Theory of Planned Behaviour (TPB). This study found that the predominant motivations for non-compliant behaviour included fatigue from information overload, government- and socially-induced distrust, as well as self-reported personality traits. In contrast, compliant individuals emphasised community-based obligations and their trust in official communications. Although participants recognised the pandemic as a challenging time, they were generally unsatisfied with the credibility, consistency, and accessibility of public health messaging. This investigation contributes to health communications studies by adopting a qualitative approach and providing insights into an under-researched demographic.